Synthesis of Functionalized Diethyl(pyrrolidin-2-yl)phosphonate and Diethyl(5-oxopyrrolidin-2-yl)phosphonate - Iwona E. Głowacka; Anna Hartwich; Iwona Rozpara; Dorota G. Piotrowska (Molecules, 2021)
Short and efficient syntheses of functionalized (pyrrolidin-2-yl)phosphonate and (5-oxopyrrolidin-2-yl)phosphonate have been developed. The synthetic strategy involved the diastereospecific 1,3-dipolar cycloaddition of N-benzyl-C-(diethoxyphosphoryl)nitrone to cis-1,4-dihydroxybut-2-ene and dimethyl maleate, respectively. O,O-Diethyl 3-carbamoyl-4-hydroxy(5-oxopyrrolidin-2-yl)phosphonate was obtained from O,O-diethyl 2-benzyl-4,5-dimethoxycarbonyl(isoxazolidin-3-yl)phosphonate by hydrogenation and subsequent treatment with ammonia, whereas transformation of O,O-diethyl 2-benzyl-4,5-dihydroxymethyl(isoxazolidin-3-yl)phosphonate into O,O-diethyl 3-aminomethyl-4-hydroxy(pyrrolidin-2-yl)phosphonate was accomplished by mesylation followed by hydrogenolysis to undergo intramolecular cyclization and the introduction of amino group via ammonolysis. Stereochemistry of the isoxazolidine cycloadducts, as well as the final functionalized (pyrrolidin-2-yl)- and (5-oxopyrrolidin-2-yl)phosphonates were established based on conformational analyses using vicinal H–H, H–P, and C–P couplings and supported by the observed diagnostic NOESY correlation signals.